A Sound Approach to Noise and Health - van Kamp, Irene; Woudenberg, Fred.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book highlights the negative and positive health effects of chronic exposure to environmental sound. It describes the state of the art in the field from a public health point of view and puts it in a broad societal perspective looking at sound from physical, social, psychological, economic and governance angles. Rather than a mere collection of papers around the theme as usually provided in special issues, this book offers a comprehensive look at the meaning of sound in society and its impacts and provides directions to further advance the field. .
1. Introduction -- 2. Summary of the evidence -- 3. Outlook -- 4. Governance (at EU and Global level).
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Acoustics; Noise control; Medicine, Preventive; Health promotion; Acoustical engineering; Environmental Law; Environmental sciences -- Social aspects; Acoustics; Noise Control; Health Promotion and Disease Prevention; Engineering Acoustics; Environmental Law; Environmental Social Sciences